1980
DOI: 10.1038/clpt.1980.115
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin and vitamin D metabolism

Abstract: A 2-wk course of rifampicin orally (600 mg/day) in 8 male subjects resulted in a consistent fall in plasma 25-hydroxycholecalciferol (25-OHD) levels of around 70%, accompanied by increased oxidation of antipyrine and 6 beta-hydroxycortisol (indicative of hepatic enzyme induction). Plasma levels of 1,25-dihydroxycholecalciferol, parathyroid hormone, and calcitonin were not altered. The fall in 25-OHD may represent the earliest lesion of drug-induced osteomalacia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 5 publications
1
35
1
Order By: Relevance
“…It is well-known that long term treatment with phenytoin, phenobarbital, rifampicin, or carbamazepine impairs bioavailability of vitamin D and bone mineralization, leading to osteomalacia and osteoporosis (13, 15-18, 20, 45-47). Consistent with this, it has been observed that the circulating level of 25(OH)D 3 or 1,25(OH) 2 D 3 is decreased by these drugs (18,20,48,49). In addition, osteopenia, osteoporosis, and osteonecrosis are the most significant bone disorders affecting patients suffering from HIV infection (50), and HIVinfected patients receiving antiretroviral therapy have a high prevalence of reduced bone mineral density (51).…”
Section: Figurementioning
confidence: 48%
See 1 more Smart Citation
“…It is well-known that long term treatment with phenytoin, phenobarbital, rifampicin, or carbamazepine impairs bioavailability of vitamin D and bone mineralization, leading to osteomalacia and osteoporosis (13, 15-18, 20, 45-47). Consistent with this, it has been observed that the circulating level of 25(OH)D 3 or 1,25(OH) 2 D 3 is decreased by these drugs (18,20,48,49). In addition, osteopenia, osteoporosis, and osteonecrosis are the most significant bone disorders affecting patients suffering from HIV infection (50), and HIVinfected patients receiving antiretroviral therapy have a high prevalence of reduced bone mineral density (51).…”
Section: Figurementioning
confidence: 48%
“…Indeed, long-term antiepileptic drug therapy, such as phenobarbital or carbamazepine, is a known risk factor for bone loss and fractures (13). In addition, prolonged therapy with rifampicin can cause vitamin D deficiency or osteomalacia (18), particularly in patients with marginal vitamin D stores (19). Notably, 2 weeks of rifampicin treatment reduces the levels of circulating 25-hydroxyvitamin D and 1α,25-dihydroxyvitamin D in healthy subjects (20).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover the further metabolism of the two hormones also occurs via such monooxygenases (Gustafsson & IngelmanSundberg, 1976;Shiverick & Neims, 1979). Rifampicin is known to induce cytochrome P450 mediated monooxygenase activity in man (Ohnhaus & Park, 1979;Brodie et al, 1980). Testosterone levels have been shown previously to be elevated during rifampicin treatment and the authors attributed this to induction of testosterone biosynthesis (Nocke-Finck & Breuer, 1980).…”
mentioning
confidence: 99%
“…& TUCKER, G.T. (1981 In a recent study we found that a 2 week course of the antibiotic rifampicin in eight male volunteers reduced by 70% serum levels of 25-hydroxyvitamin D (25-OHD), the major circulating metabolite of the vitamin (Brodie et al, 1980). As there was concomitant induction of hepatic monooxygenase activity, as evidenced by significant increases in the hydroxylation of antipyrine and cortisol, it seems possible that induction of vitamin D wastage pathways explained the fall in 25-OHD.…”
mentioning
confidence: 99%
“…Long-term treatment (for at least 2 weeks) with the PXR agonist rifampin results in a marked reduction in 25OHD 3 plasma levels, presumably by enhanced clearance of the hormone (Brodie et al, 1980(Brodie et al, , 1982Shah et al, 1981). This in turn would limit the availability of substrate for the formation of the biologically active 1␣,25(OH) 2 D 3 .…”
Section: Introductionmentioning
confidence: 99%